Quercetin ameliorates acute lung injury in a rat model of hepatopulmonary syndrome - Noha Abdel-Aziz Nassef; Manal S. Abd-El Hamid; Samy A. Abusikkien; Asmaa Ibrahim Ahmed (BMC, 2022)
Abstract Background Common bile duct ligation (BDL) is a rat experimental model to induce biliary cirrhosis. Lung fibrosis and pulmonary vascular angiogenesis and congestion are the most common complications of biliary cirrhosis that is known as hepatopulmonary syndrome. The aim of the present work is to investigate the acute lung injury in a BDL model and to investigate the possible protective effect of quercetin on this injury. Methods Twenty-four adult male albino rats of the Wister strain (weighing 150-250 g). Animals were divided into 3 groups, with 8 rats each: Group I: Sham-operated group (control). Group II: Bile duct ligation group (BDL) sacrificed after 28 days from the surgery. Group III: Quercetin-treated bile duct ligation group (Q-BDL) was given orally by gastric gavage in a dose of 50 mg/kg/day, starting from the 4th day of the operation until the 28th day. At the end of the experiment, at day 28, all rats were sacrificed. Lung specimens were processed to measure Endothelin B receptor gene expression by PCR, lung surfactant by ELISA, "eNO" s by immunohistochemistry. Histological assessment was done using; H&E, Masson's trichrome, PAS, toluidine blue-stained semi-thin sections, transmission electron microscope. Histomorphometric and statistical studies were done. Results BDL group showed significant increase in lung index together with mononuclear cellular infiltration denoting lung inflammatory state. Also, the significant increase in pulmonary endothelial nitric oxide synthase ("eNO" s) area percent and endothelin B receptor (ETB) gene expression indicates enhanced angiogenesis. Pulmonary surfactant concentration was significantly decreased together with thickening of interalveolar septa denoting lung injury and fibrosis. Quercetin led to significant decrease in lung index, pulmonary "eNO" s area percent, ETB gene expression and significant increase in pulmonary surfactant concentration. Quercetin treatment improved histological changes and morphometric measurements, limited mononuclear cellular infiltration and decreased perivascular and perialveolar collagen deposition. Conclusion Quercetin ameliorates the hepatopulmonary syndrome-induced lung injury through its anti-inflammatory, antioxidative and antifibrotic effects.